2019
DOI: 10.21894/jopr.2019.0005
|View full text |Cite
|
Sign up to set email alerts
|

THEORETICAL APPROACH OF DFT B3LYP/6-31G (d, p) ON EVALUATING THE PERFORMANCE OF tert-BUTYLHYDROQUINONE AND FREE FATTY ACIDS IN INHIBITING THE OXIDATION OF PALM OLEIN

Abstract: The effects of adding palmitic acid (PA) and linoleic acid (LA) on the performance of tert-Butylhydroquinone (TBHQ), in inhibiting the autoxidation of palm olein was studied. These fatty acids were employed to test their effectiveness on antioxidant performance, experimentally and theoretically. In experimental studies, palm olein added with fatty acids at four different concentrations in the presence or in the absence of TBHQ were heated in the oven at 60°C for 15 days and collected after 0, 1, 3, 6, 10 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The magnitude of any of thermodynamic dynamic parameters as well as energy of a system is size-dependent. This assertion is reflected in the results presented in Table 4 for which the values of all the calculated parameters increase with the increasing chain length of terminal alkoxy chain [ 44 , 45 , 46 , 47 , 49 ]. Moreover, the similar values predicted for the energy indicators of the corresponding members of the two isomers is due fact that they have the same molecular formula but only differ in configurations which do not significantly affect the energy.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The magnitude of any of thermodynamic dynamic parameters as well as energy of a system is size-dependent. This assertion is reflected in the results presented in Table 4 for which the values of all the calculated parameters increase with the increasing chain length of terminal alkoxy chain [ 44 , 45 , 46 , 47 , 49 ]. Moreover, the similar values predicted for the energy indicators of the corresponding members of the two isomers is due fact that they have the same molecular formula but only differ in configurations which do not significantly affect the energy.…”
Section: Resultsmentioning
confidence: 80%
“…On the part of the molecular electrostatic potential (MEP) presented in Figure 6 , the red cloud above the carbonyl and phenolic oxygen atoms indicates low electrostatic potential but high electron density. On the other hand, the blue cloud over the phenolic hydrogen portrays high electrostatic potential with low electron density [ 45 , 46 , 47 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…The p -chlorocalix[4]arene acted as molecular host, and three selected guest drugs namely paracetamol, ibuprofen, and cetirizine, acted as the guest molecules. The result showed that both hydrogen bonding and π-π interactions combined to stabilize the molecular structures [2] . Theoretical models proposed by Gaussian were applied to measure the optimization energy, binding energy, and interaction energy of p -chlorocalix[4]arene with the drugs.…”
Section: Data Descriptionmentioning
confidence: 99%
“…The molecular geometries of the L-ascorbic acid derivative, the cisplatin, and the prepared Pt(II) complex were fully optimized using G 09W (Chattaraj & Poddar, 1999;Caruso et al, 2012;Sabounchei et al, 2015;Ali et al, 2019;). The optimized structures and natural bond charges are presented in Figure 13.…”
Section: Dft Calculationsmentioning
confidence: 99%
“…The η values and ΔE are given in Table 4. The transition is easier in the Pt(II) complex than in the ligand and the cisplatin; the ΔE of the complex is 0.133, the ligand is 0.205, and the cisplatin is 0.161 (McGuire et al, 1984;Bakalova et al, 2009;Mansour, 2013;Elghalban et al, 2014;Sabounchei et al, 2015;Soliman et al, 2016;Ali et al, 2019) and hence the complex is softer (η= (0.006) than in the ligand 0.102 and the cisplatin 0.080) (Chattaraj & Poddar, 1999). The electronic energy and the dipole moments are tabulated in Table 4.…”
Section: Dft Calculationsmentioning
confidence: 99%